The Meaning of Profit in Immigrant Java Perspective - Ayu Rakhma Wuryandini; Lukman Pakaya (International Journal of Accounting & Finance in Asia Pasific (IJAFAP), 2020)
The purpose of this study is to understand the meaning of "profit" in the perspective of Javanese who emigrated in Gorontalo. The results of this paper are expected to be useful for Javanese immigrant to realize the meaning of "profit" and can add to the scientific treasury in the field of accounting that earnings have meaning from different perspectives. Husserl's transcendental phenomenology approach is used to answer research questions and informant experiences based on awareness. The researcher obtained the results of the study that the material profit obtained was understood by the informant namely Mrs. Sulami that the profit was meant to " meet the needs of the family ", so that what is needed in the family can be fulfilled. And profit is also interpreted as " disturbance of worship " which in the sense is a form of gratitude for the results obtained, which is a profit as a provision for worship in the hereafter through group study every week.